Staking claim to entitlements under MGNREGA: How can women make their demands? - Raghunathan, Kalyani; Kosec, Katrina; Kyle, Jordan; Narayanan, Sudha; Ray, Soumyajit (India Forum, 2024)
There are internal constraints and structural barriers to women’s claim-making under MGNREGA. Supporting more egalitarian decision-making within the village, designing interventions that can help women gain confidence to speak out in public and making officials more responsive could all help.